Effects of Imatinib Mesylate on Renin-Angiotensin System (RAS) Activity During the Clinical Course of Chronic Myeloid Leukaemia - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2009)
The renin-angiotensin system (RAS) is involved in cell growth, proliferation and differentiation in bone marrow in an autocrine-paracrine manner, and it modulates normal and neoplastic haematopoietic cell proliferation. This study aimed to assess expressions of the RAS components, renin, angiotensinogen and angiotensin-converting enzyme (ACE), during imatinib mesylate treatment of patients with chronic myeloid leukaemia (CML). Expressions of RAS components were studied in patients with CML at the time of diagnosis (n = 83) and at 3, 6 and 12 months after diagnosis (n = 35) by quantitative real-time polymerase chain reaction. De novo CML patients had increased ACE, angiotensinogen and renin mRNA levels and these expression levels decreased following administration of imatinib. The RAS activities were significantly different among Sokal risk groups of CML, highlighting the altered biological activity of RAS in neoplastic disorders. The results of this study confirm that haematopoietic RAS affects neoplastic cell production, which may be altered via administration of tyrosine kinase inhibitors such as imatinib mesylate.
Keywords: IMATINIB MESYLATE THERAPY; TYROSINE KINASE INHIBITORS; CHRONIC MYELOID LEUKAEMIA, RENIN-ANGIOTENSIN SYSTEM (RAS); RENIN; ANGIOTENSINOGEN; ANGIOTENSIN-CONVERTING ENZYME (ACE); HEMATOPOIETIC STEM-CELLS; BONE-MARROW; EXPRESSION; CARDIOTOXICITY; HYPOTHESIS; IMPACT